The role of the Epstein-Barr virus-encoded BARF1 gene expressed in human gastric epithelial cells - Li, Shuying; Zhang, Fang; Li, Ji; Hu, Xuya; Zhao, Wei; Zhang, Ke; Li, Jintao (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The study aimed to explore the effects of Epstein-Barr virus–-encoded BARF1 in human gastric epithelial cells (GES-1). Materials and Methods: A eukaryotic expression vector carrying BARF1 gene (pcDNA3.1-BARF1) was constructed. The pcDNA3.1-BARF1 was transfected into GES-1 cells, and they were selected by G418. The GES-1 cells lines that expressed BARF1 (GES-1-BARF1) were obtained. The cycle of GES-1-pcDNA3.1 cells (GES-1 cells transfected with empty vector), GES-1-BARF1 cells (GES-1 cells transfected with BARF1), and TPA-GES-1-BARF1(GES-1-BARF1 cells stimulated by 12-O-tetradecanoylphorbol-13-acetate (TPA) were analyzed by flow cytometry. Colony formation in soft agar and tumorigenicity of the transfected cells in mice with severe combined immunodeficiency (SCID) were also observed. Results: The morphology of GES-1-BARF1 cells were changed from the original shuttle to round, the adhesion between the cells and bottle wall was weakened, and the cells showed overlapping growth. The proliferation rate of GES-1-BARF1 and TPA-GES-1-BARF1 cells were faster than GES-1 and GES-1-pcDNA3.1 cells; the S phase was significantly prolonged for GES-1-BARF1 and TPA-GES-1-BARF1. GES-1-BARF1 and TPA-GES-1-BARF1 cells formed colonies in soft agar, with a cloning rate of 24.2% (58/240) and 40.0% (96/240), respectively; GES-1 and GES-1-pcDNA3.1 cells did not form colonies in soft agar. Tumors were formed in mice with SCID after injecting TPA-GES-1-BARF1 cell groups. Tumor formation did not occur in mice with SCID after injecting GES-1 and GES-1-pcDNA3.1 cell groups, but nodules were formed in the mice with SCID after injecting GES-1-BARF1 cell groups. Conclusion: GES-1-BARF1 cells malignant transformation was induced by transfected BARF1 gene and TPA stimulation. This result indicated that tumor formation not only require oncogenes, but also the stimulation of cancer-promoting substance.